Network of Opportunity : Architecture as a Medium for Upliftment of the Urban Poor Through the Activation of Derelict Urban Spaces - Hugo, Mr Jan (University of Pretoria, 2019)
Mini Dissertation (MArch(Prof)) University of Pretoria, 2018.